Knowing the Big Data - Camargo-Vega, Juan José; Camargo-Ortega, Jonathan Felipe; Joyanes-Aguilar, Luis (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Given the importance acquired by the term Big Data, the present investigation aims to study and analyze thoroughly the Big Data state of art. Moreover, a second objective is to study the features, tools, technologies, models and standards related to Big Data. And finally it seeks to identify the most relevant features that manage Big Data, so it can be known everything about the focus of the investigation.Regarding the methodology used in the development of the research, included to review the state of the art of Big Data, and show what is its current situation, to know the Big Data technologies, to present some of the NoSQL databases, which are those that allow to process unstructured data formats. Also display data models and the analysis technologies they offer, to end with some benefits from Big Data.The methodology desing used in this investigation, was not experimental, because no variables are manipulated, neither exploratory ones, because with the present investigation, only begins to know the Big Data evirioment.